IDENTIFIKASI DAN ANALISIS RISIKO PADA PROYEK PEMBANGUNAN GEDUNG SMP NEGERI 16 DENPASAR: Risk Identification And Analysis In Building Construction Projects SMP Negeri 16 Denpasar - Lestari, I Gusti Agung Ayu Istri; Diputera , I Gede Angga; Hermawan, I Putu Yana; Wea, Clarita Patricia (Ganec Swara, 2025)
The construction of the SMP Negeri 16 Denpasar building is located at Jalan Kertha Winangun No. 1 in Sidakarya Village, South Denpasar. The purpose of this study is to identify and evaluate the risks associated with the construction of the SMP Negeri 16 Denpasar building. This study uses a qualitative descriptive method, namely field research that uses data and information obtained through respondents as subjects to obtain holistic general picture answers regarding the matters studied. Risk identification is obtained through interviews and surveys to obtain possible risks that will occur in the construction of the SMP Negeri 16 Denpasar building. The results of the study showed that the identified risks were 32 (thirty-two) risks, namely 8 environmental risks (25%), 2 planning risks (6.3%), 2 economic risks (6.3%), financial risks (6.3%), natural risks (6.3%), 4 project risks (12.5%), technical risks (21.9%), human risks (3.1%), criminal risks (6.3%), and safety risks (6.3%). The results of the analysis of the level of risk acceptance showed that there were 2 risks (6%) included in the unacceptable category, 18 risks (56%) included in the undesirable category, 9 risks (28%) included in the acceptable category and 3 risks (10%) included in the negligible category.